Intersectional observations of the Human Brain Project's approach to sex and gender. Issue 2 (13th May 2019) - Fothergill, B. Tyr; Knight, William; Stahl, Bernd Carsten; Ulnicane, Inga
Abstract : Purpose: This paper aims to critically assess approaches to sex and gender in the Human Brain Project (HBP) as a large information and communication technology (ICT) project case study using intersectionality. Design/methodology/approach: The strategy of the HBP is contextualised within the wider context of the representation of women in ICT, and critically reflected upon from an intersectional standpoint. Findings: The policy underpinning the approach deployed by the HBP in response to these issues parallels Horizon 2020 wording and emphasises economic outcomes, productivity and value, which aligns with other "equality" initiatives influenced by neoliberalised versions of feminism. Research limitations/implications: Limitations include focussing on a single case study, the authors being funded as part of the Ethics and Society Subproject of the HBP, and the limited temporal period under consideration. Social implications: The frameworks underpinning the HBP approach to sex and gender issues present risks with regard to the further entrenchment of present disparities in the ICT sector, may fail to acknowledge systemic inequalities and biases and ignore the importance of intersectionality. Shortcomings of the approach employed by the HBP up to March, 2018 included aspects of each of these risks, and replicated problematic understandings of sex, gender and diversity. Originality/value: This paper is the first to use an intersectional approach to issues of sex and gender in the context of large-scale ICT research. Its value lies in raising awareness, opening a discursive space and presenting opportunities to consider and reflect upon potential, contextualised intersectional solutions to such issues.